1976
DOI: 10.1111/j.1365-3180.1976.tb00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and efflux of chloro‐s‐triazines by Setaria roots*

Abstract: Summary: The absorption and loss of four chloro‐s‐triazines was investigated in excised roots of four Setaria taxa. Different taxa absorbed the various triazines at different rates. In general, triazine absorption was greater at 2°C than at 22.5°C, and absorption rates were linear functions of external concentrations. Efflux studies showed marked differences in the rate of loss of 14C‐atrazine, 14C‐simazine, and 14C‐propazine from root sections of robust white foxtail (Setaria viridis var. robustaalba Schreibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 16 publications
5
43
1
Order By: Relevance
“…This arsenate is found to affect the root development and reduce the plant height of one variety of rice (Abedin et al 2002a). Some studies have reported that plant roots are unable to accumulate the essential nutrients from soil in the presence of excess arsenic because As(III) reacts with the sulphydryl groups of proteins (Speer 1973), causing disruption of root functions of plants (Orwick et al 1976). …”
Section: Resultsmentioning
confidence: 98%
“…This arsenate is found to affect the root development and reduce the plant height of one variety of rice (Abedin et al 2002a). Some studies have reported that plant roots are unable to accumulate the essential nutrients from soil in the presence of excess arsenic because As(III) reacts with the sulphydryl groups of proteins (Speer 1973), causing disruption of root functions of plants (Orwick et al 1976). …”
Section: Resultsmentioning
confidence: 98%
“…It is known that arsenite reacts with sulfhydryl groups of proteins of roots (Speer 1973) causing disruption of the root function (Isensee et al. 1971; Orwick et al. 1976) and even cellular death.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern of distribution, in which a large fraction of the herbicide is retained in the stem tissue below the transpiring leaves could be due to the adsorption of atrazine in the stem apoplast. However, since atrazine has been shown not to bind to cell walls (20,22,24,39), the large fraction of atrazine retained in the stem tissue can be explained by penetration of the molecule into the symplast. Atrazine has been demonstrated to freely and reversibly penetrate the symplast of corn root tissue and protoplasts (6), potato tuber tissue (22), barley roots (30,31), and velvet leaf (Abutilon theophrasti) roots (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Herbicides which move in the symplastic transport pattern were thought to be preferentially absorbed into the symplast, and subject to long-distance transport in the phloem (1). More recent experimental evidence has demonstrated that several compounds which display the apoplastic transport pattern easily penetrate the plasmalemma ofplant cells (6,20,22,24,25,30,31).…”
mentioning
confidence: 99%